Find the roots of the equation 6x2 - - 2 = 0 by the
Factorization of the corresponding quadratic polynomial.
Asked by Topperlearning User | 7th Nov, 2013, 09:52: AM
The corresponding quadratic polynomial can be factorized as below.
6x2-3+2-2 = 0
3x(2x-)+(2x-) = 0
Now, 6x2-x-2=0 gives (3x+)(2x-) =0, i.e., (3x+)=0 or (2x-)=0
Therefore, the roots of the given quadratic equation are - and
Answered by | 7th Nov, 2013, 11:52: AM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number